2.4 GHz Microstrip Antenna Arrays - Othman, Abdul Rani; Wasli, Chairulsyah; Ahmad, Mohd Riduan (2007)
This paper described the design, simulation and fabrication of the microstrip patch antennas at 2.4 GHz using one element, arrays 2 elements and four elements. The antennas have been modeled using microstrip lines and S parameter data from individual single element. The data is extracted from the simulation and combined with the microstrip transmission line. The properties of antennas such as bandwidth return loss and voltage standing wave ratio (VSWR) have been investigated and compared between simulation and measurements. Furthermore, the return losses of the antennas are below -10 dB from both simulation and measurement.